Association of non-linear dynamics of heart rate variability with all-cause mortality in patients with sarcoidosis - Giallafos, Elias; Ilias, Ioannis; Katsanos, Spiros; Kolilekas, Likourgos; Manali, Efrosini; Vakrakou, Aglaia; Papaioannou, Theodore; Zisimos, Kostas; Seitaridi, Gethsimani; Parisis, Giannis; Koulouris, Nikos; Papiris, Spiros (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Sarcoidosis (Sarc) is linked to increased morbidity and mortality. While 24-hour ambulatory ECG recording is essential for evaluating patients with cardiac symptoms, the complementary role of heart rate variability (HRV) for risk stratification in Sarc patients remains undefined. The aim of this observational study was the assessment of non-linear indices of HRV as independent predictors of mortality in Sarc. Methods: 317 patients with confirmed diagnosis of Sarc, underwent comprehensive conventional cardiac testing, including Cardiac Magnetic Resonance (CMR) with late gadolinium enhancement (LGE). These patients were followed up for all-cause mortality as endpoint. Each patient underwent twenty-four-hour Holter monitoring, from which approximate entropy (APEN), short and long-term detrended fluctuation analysis (DFAα1 and DFAα2, respectively), as well as other HRV parameters, were calculated. Results: The study recruited 317 patients (137 men, 180 women) with a mean age of 48.22 ± 11.88 years. Over a median follow-up period of approximately 48 months, 17 deaths were recorded. Competing risk analysis revealed that decreased DFAα1 was a robust prognostic indicator for increased total mortality. ROC analysis demonstrated that the area under the curve (AUC) of DFAα1 (< 0.95) for predicting mortality was 0.761 (95% confidence interval (CI) = 0.617–0.905). DFAα1 ≥ 0.95 was associated with total mortality (HR = 0.109, 95% CI = 0.033–0.362, P= 0.0003). Conclusion: Evaluation of cardiac autonomic dysfunction by DFAα1 serves as an independent predictor for all-cause mortality in patients with Sarc.